Preparation and Characterization of Pure Rutile TiO2 Nanoparticles for Photocatalytic Study and Thin Films for Dye-Sensitized Solar Cells. (19th September 2010) - Chen, Huei-Siou; Su, Chaochin; Chen, Ji-Lian; Yang, Tsai-Yin; Hsu, Nai-Mu; Li, Wen-Ren
Abstract : Pure rutile-phase TiO2 (r-TiO2 ) was synthesized by a simple one pot experiment under hydrothermal condition using titanium (IV) n-butoxide as a Ti-precursor and HCl as a peptizer. The TiO2 products were characterized by XRD, TEM, ESCA, and BET surface area measurement. The r-TiO2 were rodlike in shape with average size of 61 × 32 nm at hydrothermal temperature of 220°C for 10 h. Hydrothermal treatment at longer reaction time increased the tendency of crystal growth and also decreased the BET surface area. The degradation of methylene blue was selected as a test reaction to confer the photocatalytic activity of as-obtained r-TiO2 . The results showed a strong correlation between the structure evolution, particle size, and photocatalytic performance of r-TiO2 . Furthermore, the r-TiO2 -based solar cell was prepared for the photovoltaic characteristics study, and the best efficiency of 3.16% was obtained.